Validity of suicide statistics in Europe in relation to undetermined deaths: developing the 2-20 benchmark. Issue 5 (10th December 2011) - Värnik, Peeter; Sisask, Merike; Värnik, Airi; Arensman, Ella; Van Audenhove, Chantal; van der Feltz-Cornelis, Christina M; Hegerl, Ulrich
Abstract : Background: The suicide rate is a macro indicator of the population's psychosocial wellbeing and an evaluation criterion of the effectiveness of suicide prevention strategies. A high level of injury deaths of undetermined intent (UD) is usually discussed in connection with the validity of suicide statistics. An effort is made to develop a criterion to characterise the quality of suicide statistics. Methods: Standardised rates of suicides (X60–X84) and UD (Y10–Y34) by the International Classification of Disease version 10 as an average for the past five available years were taken from the WHO European mortality database. Rate ratios were computed by dividing rates of UD by suicide rates. Results: There is considerable variation in suicide and UD rates among countries. The highest overall rates of UD were registered in Russia, Ukraine and Belarus, and the lowest in Greece, Spain and Italy. The EU-15 average UD rate of 1.97 and the rate ratio of 0.194 UD to suicides were combined into a '2-20 benchmark', in which the primary indicator is 2.0 UD cases per 100 000 and the secondary indicator is the proportion of UD to suicides 0.20 (20%), which enables countries to be clustered according to the quality of suicide statistics. The following countries satisfied the benchmark: Greece, Norway, Spain, The Netherlands, Luxembourg, France, Austria, Italy, Romania, Hungary, Ireland and Finland. Conclusion: This study used the developed '2-20 benchmark' in Europe to assess suicide registration quality in a particular country, to compare the relative position of countries, and to set a target for those European countries that have not yet achieved the benchmark.